2018
DOI: 10.1186/s12870-018-1556-2
|View full text |Cite
|
Sign up to set email alerts
|

Preharvest application of ethephon and postharvest UV-B radiation improve quality traits of beetroot (Beta vulgaris L. ssp. vulgaris) as source of colourant

Abstract: BackgroundBetanins have become excellent replacers for artificial red-purple food colourants. Red beet (Beta vulgaris L. spp. vulgaris) known as beetroot, is a rich source of betalains, which major forms are betanin (red to purple) and vulgaxanthin (yellow). Betalains and phenolic compounds are secondary metabolites, accumulation of which is often triggered by elicitors during plant stress responses. In the present study, pre-harvest applications of ethephon (an ethylene-releasing compound) and postharvest UV-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 44 publications
0
12
0
Order By: Relevance
“…In 2016, °Brix in treated grapes was not significantly different when compared with the control, although the °Brix values of ethephon‐treated berries tended to be slightly lower than those of the control (Figure 1). The decrease in the accumulation rate of soluble solids has been observed after preharvest treatments of ethephon in other species such as Beta vulgaris L. (Barba‐Espin et al., 2018) or Capsicum annuum L. (Yang, Luo, Tan, & Kan, 2020). However, other authors have reported no significant differences in sugar accumulation in V. vinifera L. (Kok & Bal, 2018) or Solanum lycopersicum L. (Martínez‐Damián, Cano‐Hernández, Moreno‐Pérez, Del Castillo, & Cruz‐Álvarez, 2018).…”
Section: Resultsmentioning
confidence: 94%
“…In 2016, °Brix in treated grapes was not significantly different when compared with the control, although the °Brix values of ethephon‐treated berries tended to be slightly lower than those of the control (Figure 1). The decrease in the accumulation rate of soluble solids has been observed after preharvest treatments of ethephon in other species such as Beta vulgaris L. (Barba‐Espin et al., 2018) or Capsicum annuum L. (Yang, Luo, Tan, & Kan, 2020). However, other authors have reported no significant differences in sugar accumulation in V. vinifera L. (Kok & Bal, 2018) or Solanum lycopersicum L. (Martínez‐Damián, Cano‐Hernández, Moreno‐Pérez, Del Castillo, & Cruz‐Álvarez, 2018).…”
Section: Resultsmentioning
confidence: 94%
“…In most studies where UV-B radiation has been manipulated, it has been applied prior to harvest (i.e., preharvest), or following harvest (i.e., postharvest). Species studied in this context include beetroot [ 200 ], broccoli [ 201 ], ginseng [ 202 ], prickly pear [ 203 ], blueberry [ 204 ], and even mushrooms [ 205 ]. In certain varieties of peach, these treatments have helped maintain the weight, firmness, and vitamin C content of the fruit, which increases its quality, value, and shelf-life [ 206 208 ].…”
Section: Terrestrial Ecosystems and Biodiversitymentioning
confidence: 99%
“…87 However, after three and seven days of storage, vulgaxanthin I content in beets decreased, regardless of whether the samples were control or UV-B treated. 87 Betalain pigments may also play some role in protecting against UV stress, but further evidence is needed to support this hypothesis.…”
Section: ■ Effects On Bioactive Compoundsmentioning
confidence: 95%
“…They contain two groups of water-soluble pigments: red-purple betacyanidins and yellow betaxanthins. Betacyanidins are conjugates of cyclo-dihydroxyphenylalanine and betalamic acid, and betaxanthins are conjugates of amines or amino acids and betalamic acid …”
Section: Effects On Bioactive Compoundsmentioning
confidence: 99%